STUNTED PLANT 1 Mediates Effects of Cytokinin, But Not of Auxin, on Cell Division and Expansion in the Root of Arabidopsis - Beemster, Gerrit T.S. (American Society of Plant Physiologists, 2000)
Plants control organ growth rate by adjusting the rate and duration of cell division and expansion. Surprisingly, there have been few studies where both parameters have been measured in the same material, and thus we have little understanding of how division and expansion are regulated interdependently. We have investigated this regulation in the root meristem of the stunted plant 1 (stp1) mutation of Arabidopsis, the roots of which elongate more slowly than those of the wild type and fail to accelerate. We used a kinematic method to quantify the spatial distribution of the rate and extent of cell division and expansion, and we compared stp1 with wild type and with wild type treated with exogenous cytokinin (1 μm zeatin) or auxin (30 nm 2,4-dichlorophenoxyacetic acid). All treatments reduced average cell division rates, which reduced cell production by the meristem. Auxin lowered root elongation by narrowing the elongation zone and reducing the time spent by a cell in this zone, but did not decrease maximal strain rate. In addition, auxin increased the length of the meristem. In contrast, cytokinin reduced root elongation by lowering maximal strain rate, but did not change the time spent by a cell within the elongation zone; also, cytokinin blocked the increase in length and cell number of the meristem and elongation zone. The cytokinin-treated wild type phenocopied stp1 in nearly every detail, supporting the hypothesis that cytokinin affects root growth via STP1. The opposite effects of auxin and cytokinin suggest that the balance of these hormones may control the size of the meristem.